An investigation of the effects of an awareness campaign on young residents’ perceptions: a case study of the Lenggong World Heritage Site - Jaafar, Mastura; Rasoolimanesh, Mostafa S.; Md Noor, Shuhaida (Routledge, 2015)
This paper investigates three issues concerning younger residents of the Lenggong Valley World Heritage Site (WHS) in Malaysia: their perceptions of tourism development, their perceptions and attitudes regarding their contribution to and promotion of the WHS, and the effects of an awareness campaign regarding the benefits of tourism development and WHS recognition on their perceptions. The awareness campaign was based on social exchange theory. A questionnaire was administered to secondary school students in Lenggong before and after the campaign. Responses revealed that younger residents have overall positive perceptions of tourism development and WHS recognition, and that they want to contribute towards promoting and supporting the WHS. Significant pre- and post-campaign differences in perceptions of younger residents demonstrate the importance of awareness regarding the benefits of tourism development and WHS recognition. The findings have implications for key stakeholders in the promotion of sustainable tourism development and conservation programmes in Lenggong.